2009
DOI: 10.1111/j.1574-6941.2009.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and postdeposition mechanisms as possible drivers of microbial population variability in glacier ice

Abstract: Glaciers accumulate airborne microorganisms year by year and thus are good archives of microbial communities and their relationship to climatic and environmental changes. Hypotheses have focused on two possible drivers of microbial community composition in glacier systems. One is aeolian deposition, in which the microbial load by aerosol, dust, and precipitation events directly determines the amount and composition of microbial species in glacier ice. The other is postdepositional selection, in which the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 78 publications
(156 reference statements)
6
55
0
Order By: Relevance
“…The conclusive finding of the present study was the existence of abundant, viable and diverse indigenous microbial populations in the NEEM Greenland ice core, at depths ranging from 100 to 2051 m. Our study also provided new evidence confirming the previously found direct correlation between microbial cell abundance in polar and non-polar ice cores and deposition climate, with higher numbers of cells found in ice layers deposited during colder climate periods versus lower cell abundance in ice core layers deposited during warmer climates (Abyzov 1993;Xiang et al 2005;Yao et al 2006;Miteva et al 2009;Xiang et al 2009). Furthermore, detecting viable cells in ice deposited 300Á80 000 years ago and recovering diverse isolates (albeit at a low culturability levels) showed once again that microbial cells are capable of long-term survival trapped in one of the harshest environments on Earth.…”
Section: Discussionsupporting
confidence: 79%
“…The conclusive finding of the present study was the existence of abundant, viable and diverse indigenous microbial populations in the NEEM Greenland ice core, at depths ranging from 100 to 2051 m. Our study also provided new evidence confirming the previously found direct correlation between microbial cell abundance in polar and non-polar ice cores and deposition climate, with higher numbers of cells found in ice layers deposited during colder climate periods versus lower cell abundance in ice core layers deposited during warmer climates (Abyzov 1993;Xiang et al 2005;Yao et al 2006;Miteva et al 2009;Xiang et al 2009). Furthermore, detecting viable cells in ice deposited 300Á80 000 years ago and recovering diverse isolates (albeit at a low culturability levels) showed once again that microbial cells are capable of long-term survival trapped in one of the harshest environments on Earth.…”
Section: Discussionsupporting
confidence: 79%
“…This implies the presence of inactive nitrifying and denitrifying populations, attributed to the shortage of ammonium and nitrate. Obviously, at the initial stage of the glacier forefield, sufficient N and C are provided for mineralization: (i) allochthonous organic material (plant debris, insects and so on) is deposited in the forefield, as revealed by our and other measurements ( (Table 1), (ii) the cryoconite holes in the glacier ablation zone possibly inhabit small foodwebs of cyanobacteria and heterotrophs, which were relocated to the glacier forefield by the glacial stream after snowmelt (Schmalenberger and Noll, 2009;Xiang et al, 2009) and (iii) microbes might feed on ancient recalcitrant C (Hodkinson et al, 2002;Bardgett et al, 2007). In addition, significant inputs of nutrients may be due to atmospheric dry and wet deposition of N and C species (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Although the potential for depositional and postdepositional processes to influence the structure of these microbial communities is proposed (Xiang et al, 2009b), our understanding of the scale of spatial and temporal variation of snow community composition is limited, in spite of the extensive global areal extent of snow cover. This study therefore offers the first quantitative evidence from 16S rRNA gene-based community structure profiling and amplicon pyrosequencing that different snowpack-associated habitats from a High Arctic glacier harbour distinct and diverse bacterial communities, and that these can be temporally dynamic within the melting season.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that the 'surface snow' bacterial community is strongly influenced by organisms introduced by aeolian (or 'dry') deposition. In contrast, snow (and by extension, its decomposition product, slush) constitutes predominantly 'wet', or precipitation-related deposition (Xiang et al, 2009b); all analyses differentiate snow and slush with surface snow in terms of community composition. Glacial ice is likely to integrate microbes introduced by both deposition mechanisms, and thus may conserve dry-deposited microbes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation